Prognostic significance of steroid response in pediatric acute lymphoblastic leukemia: The CCCG-ALL-2015 study - Chu, Jinhua; Cai, Huaju; Cai, Jiaoyang; Bian, Xinni; Cheng, Yumei; Guan, Xianmin; Chen, Xiaoqian; Jiang, Hua; Zhai, Xiaowen; Fang, Yongjun; Zhang, Lei; Tian, Xin; et al. (Frontiers in Oncology, 2022)
Introduction Whether steroid response is an independent risk factor for acute lymphoblastic leukemia (ALL) is controversial. This study aimed to investigate the relationship between response to dexamethasone and prognosis in children with ALL. Methods We analyzed the data of 5,161 children with ALL who received treatment in accordance with the Chinese Children’s Cancer Group ALL-2015 protocol between January 1, 2015, and December 31, 2018, in China. All patients received dexamethasone for 4 days as upfront window therapy. Based on the peripheral lymphoblast count on day 5, these patients were classified into the dexamethasone good response (DGR) and dexamethasone poor response (DPR) groups. A peripheral lymphoblast count ≥1× 109/L indicated poor response to dexamethasone. Results The age, white blood cell counts, prevalence of the BCR/ABL1 and TCF3/PBX1 fusion genes, and rates of recurrence in the central nervous system were higher in the DPR than in the DGR group (P<0.001). Compared to the DPR group, the DGR group had a lower recurrence rate (18.6% vs. 11%) and higher 6-year event-free survival (73% vs. 83%) and overall survival (86% vs. 92%) rates; nevertheless, subgroup analysis only showed significant difference in the intermediate-risk group (P<0.001). Discussion Response to dexamethasone was associated with an early treatment response in our study. In the intermediate-risk group, dexamethasone response added a prognostic value in addition to minimal residual disease, which may direct early intervention to reduce the relapse rate.